A Phenomenological Study of Lived Experience of Worker’ Strike (Case Study: Workers of Copper Complex of Shahr Babak) - Ramjerdi, Vahideh Gholamian; Khoddami, Ali Reza; Karimi, Majid Reza (International Journal of Psychosocial Rehabilitation, 2020)
Industrialization of societies has given rise to new social relations among the actors and as a result, numerous social problems and issues have followed. The phenomenon of workers’ strike is of a social and economic nature and is the result of industrial transformation and conflict between the actors. To study this phenomenon, one needs not only to pay attention to the general economic and social conditions rather to the intentions, thoughts and mentalities of the actors too. Then, in this study we struggle to understand the lived experience of workers of strike and explore their experiences of this social event as well as the related issues and challenge of strike in general. The method of present study is qualitative and its strategy is phenomenology. The data have been gathered through the technique of semi-structured interview. The participants in this study have been chosen using the method of purposeful sampling from among the workers of Copper Complex of Shahr Babak who had experienced strike in past years. For analysis of data and excavation of main and secondary themes, we have made use of Colaizzi’s seven-leveled method (1978). The analysis of the lived experience of workers’ strike led to the identification of 11 main themes: motivating derives, cognitive interpretation, perspective of strike, perspective of family, justification and legitimization of strike, strategy of action, type of action, forms of strike, individual reactions/ third group, individual and social challenges, and individual and social outcomes. Exploration of experiences of workers of strikers has shown that they have taken part first in the strike under the influence of motivational-economic-vocational and social-psychological stimuli but in the course of strike, such cases as cognitive interpretation, type of perspective, type of justification and legitimization, reactions of third person and group as well as individual and social challenges conduct the process and quality of activity and protest of these workers and finally lead to individual and social outcomes. The understanding acquired through the lived experience of workers’ experience can facilitate the management of this phenomenon in the society.